Governance in the COVID -19 era: Expectations on water services - Carreón-Guillén, Javier (2022)
The system of co-management and co-administration of public services known as governance has been widely discussed in terms of its dimensions, but so far, no analysis of the process has been established. This is the case of the relationship between governance and elections. It is in the electoral contest where the conflict between the parties begins due to the preferences, intentions to vote and votes of the electorate. The rulers propose increases in rates for those who can pay them, but suggest subsidies and forgiveness for vulnerable sectors. The differences between the rulers and the ruled reveal a governance expected by the parties involved. The objective of this work has been to confirm the factorial structure reported in the literature. Two studies, one exploratory and one confirmatory, were conducted during the 2021 elections in the context of the Mexico City pandemic. The factorial structure of the Expected Governance Scale of Carreón (2020) was established, establishing three factors: expected resolution, perceptions of agreements and expectations of responsibilities, although the research design limited the findings to the analysis sample, suggesting the extension of the model to other moderating factors such as leadership.